2004 IEEE/PES Transmision and Distribution Conference and Exposition: Latin America (IEEE Cat. No. 04EX956)
DOI: 10.1109/tdc.2004.1432488
|View full text |Cite
|
Sign up to set email alerts
|

An OPF based tool for demand relief programs

Abstract: Abstrucf-Tbis paper proposes a Dynamic Opthal PowerFlow @OPQ framework to assist the implementation of consumer participation programs aimed at mitigating the effects of critical operating conditions on the quality of power supply. The proposed DOPF-based tool allows the representation of consumer operating constraints and provides important subsidies to the implementation of consumer participation programs, such as the proper selection of the loads to be reduced and the corresponding reduction of MW/MVAr cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Equation (13) represents the dynamic constraints. When (8) and (9) are both included in dynamic constraints, the size of dynamic constraints is…”
Section: Primal-dual Interior Point Methods Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Equation (13) represents the dynamic constraints. When (8) and (9) are both included in dynamic constraints, the size of dynamic constraints is…”
Section: Primal-dual Interior Point Methods Frameworkmentioning
confidence: 99%
“…For large-scale DOPF models, one major concern is to reduce the dimension of KKT system. Furthermore, observation of DOPF model (1)- (9) shows that the inequality constraints have both lower and upper bounds. Hence, the dual-bound PDIPM framework proposed in [25] is adopted to solve the large-scale DOPF models.…”
Section: Primal-dual Interior Point Methods Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of DSB on total costs, system marginal price, capacity element payments and benefit allocation between producers and consumers are examined. A tool based on OPF assessing the effects of consumer participation in power market is developed in[83].Two scenarios, price-responsive loads and consumers subject to constant tariffs, are compared to illustrate the effectiveness of consumers' participation programs. It is concluded that consumers' reduction of their energy consumption relieves critical system operating conditions, especially during critical operating conditions.…”
mentioning
confidence: 99%